Cell entry mechanisms of HSV: what we have learned in recent years. (October 2015) - Agelidis, Alex M; Shukla, Deepak
HSV type-1 and -2 are widespread pathogens producing lifelong infection with multiple sequelae, including oral, ocular and genital disease. The process of herpesvirus entry is a highly complex process involving numerous viral and cellular factors. Entry begins with attachment of virus to the cell surface followed by interactions between viral glycoproteins and cellular receptors to facilitate capsid penetration. The nucleocapsid is then transported along microtubules to the nuclear membrane, where viral DNA is released for replication in the nucleus. The work reviewed here comprises the most recent advancements in our understanding of the mechanism involved in the herpesvirus entry process.